Computational identification of most potent atom pair catalysts for electrocatalytic nitrogen reduction reaction over hydrogen evolution reaction - Verma, Tushar Singh; Dar, Afshana Hassan; Dar, Manzoor Ahmad; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Inter., 2024)
Robust electrocatalytic atom pair compositions (APCs) where Nitrogen Reduction Reaction (NRR) is more enhanced over competing Hydrogen Evolution Reaction (HER) is searched for using computational studies based on Density Functional Theory based methods. Atomic pairs are anchored on mechanically and thermally stable graphene surfaces. A wide range of transition metal based atom pair compositions from 3d, 4d, and 5d groups are systematically investigated for reduction of dinitrogen molecule with lower reduction barrier as compared to HER. APR compositions of Ni-Rh with an overall limiting potential of -0.22 V, Fe-W with an overall limiting potential of -0.26 V and Co-Pt with an overall limiting potential of -0.28 V are identified as the most potent atomic pairs for enhanced nitrogen reduction reaction over the HER. Finally, the performance of most potent composition, viz., Ni-Rh is validated to be consistent with respect to their thermodynamic stability and performance within the solvent effects.
Keywords: Atom pair catalysts; Density Functional Theory (DFT); Electrochemical nitrogen reduction reaction (eNRR); hydrogen evolution reaction (HER); IR stretching frequencies; N-N bond length

Size and morphology dependent activity of Cu clusters for CO2 activation and reduction: a first principles investigation - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad; Joshi, Krati (ChemPhysChem, 2024)
Various Cu-based materials in diverse forms have been investigated as efficient catalysts for electrochemical reduction of CO2; however, they suffer from issues such as higher over potential and poor selectivity. The activity and selectivity of CO2 electro reduction have been shown to change significantly when the surface morphology (steps, kinks, and edges) of these catalysts is altered. In light of this, size and morphology dependent activity of selected copper clusters, Cun (n=2-20) have been evaluated for the activation and reduction of CO2 molecule. The phase-space of these copper clusters is rich in conformations of distinct morphologies starting from planar, 2D geometries to prolate-shaped geometries and also high-symmetry structures. The binding efficiency and the activation of CO2 are highest for medium sized clusters (n=9-17) with prolate-morphologies as compared to small or larger sized CunCO(2) clusters that are existing mainly as planar (triangular, tetragonal etc.) or highly-symmetric geometries (icosahedron, capped-icosahedron etc.), respectively. The best performing (prolate-shaped) CunCO2 conformations are quite fluxional and also they are thermally stable, as demonstrated by the molecular dynamics simulations. Furthermore, on these CunCO(2) conformations, the step-by-step hydrogenation pathways of CO2 to produce value-added products like methanol, formic acid, and methane are exceptionally favorable and energy-efficient.
Keywords: CO2 activation; CO2 hydrogenation; Copper clusters; Density Functional Theory (DFT); molecular dynamics